GAYA KEPEMIMPINAN KHARISMATIK KIAI DALAM MENGEMBANGKAN PONDOK PESANTREN AL-ISLAMI SUMBERMULYO PESANGGARAN BANYUWANGI - Nur Hidayati; Mamlukhah (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
Charismatic leadership places more emphasis on the privileges of the leader which has an impact on the number of followers who obey and obey the leader. Charismatic leaders are expected to maintain their privileges. This study aims to: 1) find out Kiai's charismatic leadership style in developing the Al-Islami Sumbermulyo Islamic Boarding School, Pesanggaran Banyuwangi. 2). To find out the supporting and inhibiting factors of Kiai's charismatic leadership style in developing the Al-Islami Sumbermulyo Islamic Boarding School, Pesanggaran Banyuwangi. This type of research uses qualitative. The data collection methods used in this research are interviews, observation, and documentation. The data analysis technique used is interactive three models. While the validity of the data is done through triangulation. The results of this study indicate that 1. The Kyai's charismatic leadership style in developing the Al-Islami Sumbermulyo Islamic Boarding School, Pesanggaran Banyuwangi, is in accordance with the characteristics of charismatic leadership, namely: the Kiai has a strong vision, has good communication and speaking skills, istiqomah and focuses on managing pesantren, and have high self-confidence. 2. Factors supporting the development of Islamic boarding schools are the existence of volunteer teachers who are alumni of Islamic boarding schools, and the support of the general public. The inhibiting factors are regional factors and the lack of funds.